Vertical profiles of 90Sr activities in seawater in the Greenland Sea, Chukchi Sea and Arctic Ocean. (April 2019) - Huang, Dekun; Yu, Tao; Bao, Hongyan; Deng, Fangfang; Lin, Jing; Wang, Rongyuan
Abstract: The 90 Sr activities of seawater were investigated in the high-latitude region of the Arctic Ocean from August–September 2017. The 90 Sr activities in seawater in the Chukchi Sea, central Arctic Ocean and East Greenland Sea were 0.31–2.42, 0.12–1.86 and 0.13–1.20 Bq m −3, respectively. The average 90 Sr activity (0.92 Bq m −3 ) below 500 m in the central Arctic Ocean was higher than those in previous reports. Our study provided high-resolution baseline 90 Sr activity data for the whole water column in the high-latitude region of the Arctic Ocean ( 85°N). The inventory of 90 Sr in the central Arctic Ocean was higher than those in the Chukchi Sea and East Greenland Sea. The results of our study indicated that 90 Sr could be transported to the deep seawater and remain in the Arctic Ocean for a long time. Highlights: 90 Sr was observed in the Greenland Sea (GS), Chukchi Sea (CS) and Arctic Ocean. High-resolution baseline 90 Sr data in the high-latitude region was observed in 2017. The 90 Sr activities in seawater were 0.12–2.42 Bq m −3 . The 90 Sr inventory in the central Arctic Ocean was higher than that in the CS and GS.